Simulations of pH and thermal effects on SARS-CoV-2 spike glycoprotein - Niu, Ziyuan; Kementzidis, Georgios; Rafailovich, Miriam; Simon, Marcia; Papadopoulos, Evangelos; Aktas, Bertal H.; Deng, Yuefan (Frontiers in Molecular Biosciences, 2025)
We performed triplicate and long-time all-atom molecular dynamics simulations to investigate the structures and dynamics of the SARS-CoV-2 spike glycoprotein (S-protein) for a broad range of pH = 1 through 11 and temperatures of 3°C through 75°C. This study elucidates the complex interplay between pH and thermal effects on S-protein structures, with implications for its behavior under diverse conditions, and identifies the RBD as a primary region of the structural deviations. We found: 1) Structural deviations in the S-protein backbone at pH = 1 are 210% greater than those at pH = 7 at 75°C, with most of the deviations appearing in the receptor-binding domain (RBD). Smaller structural changes are observed at pH = 3 and 11. 2) The pH and thermal conditions impact on the protein structures: substantial acidic and basic conditions expand the protein’s solvent exposure, while high heat contracts. This effect is primarily pH-driven at extreme acidity and thermo-driven at moderate pH. 3) The Gibbs free energy landscape reveals that pH as the main driver of structural changes. 4) The parametrized methods enable the predictions of the S-protein properties at any reasonable pH and thermal conditions without explicit MD simulations.